Investigation of High-Intensity Implantation of Titanium Ions into Silicon under Conditions of Beam Energy Impact on the Surface - Ivanova A. I. Anna Ivanovna; Vakhrushev D. O. Dimitry Olegovich; Korneva O. S. Olga Sergeevna; Gurulev A. V. Aleksandr Valerjevich; Varlachev V. A. Valery Aleksandrovich; Efimov D. D. Dmitry Davidovich; Chernyshev A. A. (2024, 2024)
Title screen